2022
DOI: 10.1186/s13071-022-05321-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of insecticide resistance and patterns of pesticides usage in agriculture in the city of Yaoundé, Cameroon

Abstract: Background The practice of agriculture in urban settings contributes to the rapid expansion of insecticide resistance in malaria vectors. However, there is still not enough information on pesticide usage in most urban settings. The present study aims to assess the evolution of Anopheles gambiae (s.l.) population susceptibility to insecticides and patterns of pesticide usage in agriculture in the city of Yaoundé, Cameroon. Methods WHO susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 100 publications
(77 reference statements)
2
7
0
Order By: Relevance
“…to both deltamethrin and permethrin was recorded in all sites. The resistance profile detected during the present study, was in accordance with studies conducted so far across the country, suggesting rapid expansion of insecticide resistance in vector populations [ 5 , 7 , 35 ]. Similar evolution of pyrethroid resistance patterns have been reported across Africa [ 6 , 18 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…to both deltamethrin and permethrin was recorded in all sites. The resistance profile detected during the present study, was in accordance with studies conducted so far across the country, suggesting rapid expansion of insecticide resistance in vector populations [ 5 , 7 , 35 ]. Similar evolution of pyrethroid resistance patterns have been reported across Africa [ 6 , 18 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is likely that mosquitoes in the sites of Kaélé, Santchou, Kékem and Bélabo are exposed to additional selective pressure resulting from the use of pesticides in agriculture and or public health. A recent study indicated the use of a large variety of compounds, including herbicides, fungicides and insecticides, in agriculture in Cameroon [ 7 ]. Kaélé is situated in an area with intense cultivation of cotton.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…funestus populations across Cameroon. characterized by no or very low mortality rates to this compound [ 17 , 18 , 19 ]. To our knowledge, this is the first report of insecticide resistance in An.…”
Section: Discussionmentioning
confidence: 99%